2022
DOI: 10.3390/biom12071010
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Pyroptosis and Autophagy in Ischemia Reperfusion Injury

Abstract: Pyroptosis is a process of programmed cell death mediated by gasdermin (GSDM) found in recent years. In the process of pyroptosis, caspase-1 or caspase-11/4/5 is activated, which cleaves gasdermin D and separates its N-terminal pore-forming domain (PFD). The oligomers of PFD bind to the cell membrane and form macropores on the membrane, resulting in cell swelling and membrane rupture. Increasing evidence indicates that pyroptosis is involved in many diseases, including ischemia reperfusion injury. Autophagy is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 102 publications
0
5
0
Order By: Relevance
“…B355252 suppressed TLR4, NLRP3, caspase-1, IL-1β, and IL-18 in LPS-injected animals, demonstrating that B355252 is capable of inhibiting the LPS-activated pyroptosis signaling pathway. Pyroptosis has been shown to be involved in the pathogenesis of cardiovascular diseases, metabolic diseases, and neurological diseases (for reviews, see [42][43][44][45][46][47][48]). In the nervous system, pyroptosis is associated with Parkinson's disease, Alzheimer's disease, amyotrophic lateral sclerosis (ALS), and cerebral stroke.…”
Section: Discussionmentioning
confidence: 99%
“…B355252 suppressed TLR4, NLRP3, caspase-1, IL-1β, and IL-18 in LPS-injected animals, demonstrating that B355252 is capable of inhibiting the LPS-activated pyroptosis signaling pathway. Pyroptosis has been shown to be involved in the pathogenesis of cardiovascular diseases, metabolic diseases, and neurological diseases (for reviews, see [42][43][44][45][46][47][48]). In the nervous system, pyroptosis is associated with Parkinson's disease, Alzheimer's disease, amyotrophic lateral sclerosis (ALS), and cerebral stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Normally, autophagy is related to apoptosis as well as the mechanism of cell death. 28 , 29 There is a complex cross-regulation between autophagy and apoptosis, involving a variety of common regulatory factors and signal transduction pathways. 30 The initiation of autophagy protects cells from apoptosis in IVDD, highlighting its major cytoprotective role.…”
Section: Autophagy Biologymentioning
confidence: 99%
“…Some studies indicated that MSCs could attenuate the ischemia-reperfusion injury (IRI), which is a common complication of LT serving as a key limiting factor for a good outcome in the patients. Some studies revealed that MSCs could modulate oxidative stress, autophagy, and apoptosis that were closely associated with the pathogenesis of IRI [40, 41]. For instance, Wang et al [42] indicated that BM-MSCs could protect the rats against IRI by enhancing the autophagy mediated by HO-1 (heme oxygenase-1).…”
Section: Immunomodulatory Role Of Mscs In Ltmentioning
confidence: 99%